Pengaruh Penambahan STPP (Sodium Tripolyphospate) terhadap Penurunan Kadar Asam Oksalat pada Pati Talas - Nursanty Nursanty; Daniel Saputra; Budi Santoso; Yenny Sugiarti (Seminar Nasional Lahan Suboptimal, 2020)
Nursanty N, Saputra D, Santoso B, Sugiarty Y. 2020. The effect of addition of STPP (Sodium Tripolyphospate) on decreasing oxalic acid levels in taro starch. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Taro has the potential to be developed into an alternative food source due to its high nutritional content but the presence of a toxic ingredient in the form of oxalate in the tubers which can cause itching on the skin, mouth and throat. Oxalates come in two forms, namely oxalic acid and calcium oxalate. This study aims to determine the effect of STPP (Sodium Tripolyphospate) Cross-Linking on reducing levels of oxalic acid in modified taro starch. The design used in this study was a factorial randomized design with one factor. The treatment consisted of 4 levels and each treatment was repeated three times. Treatment consisted of the STPP concentration (B0 = 0%, B1 = 0.5%, B2 = 1%, B3 = 1.5%). The parameters observed were oxalic acid levels. The results of the analysis showed that the difference in the starch concentration of STPP had a significant impact on decreasing the level of oxalic acid in taro starch. The levels of oxalic acid were 11.35% at 0% STTP treatment, 7.98% at 0.5% STTP treatment and 5.04% at 1% STTP treatment and 1.5%. From the data obtained, it can be seen that the more STTP concentrations are added, the lower the oxalic acid levels in taro starch.